JavaScript functional programming for JavaScript developers : unlock the powers of functional programming hidden within JavaScript to build smarter, cleaner, and more reliable web apps : a course in three modules - Antani, Ved; Timms, Simon; Mantyla, Dan (Learning path, 2016)
Unlock the powers of functional programming hidden within JavaScript to build smarter, cleaner, and more reliable web apps About This Book Write powerful code with the high-level functions that JavaScript offers Discover what functional programming is, why it's effective, and how it's used in JavaScript Understand and optimize JavaScript's hidden potential as a true functional language Who This Book Is For If you are a JavaScript developer interested in learning functional programming, looking for the quantum leap toward mastering the JavaScript language, or just want to become a better programmer in general, then this book is ideal for you. This guide is aimed at programmers, involved in developing reactive frontend apps, server-side apps that wrangle with reliability and concurrency, and everything in between. What You Will Learn Get a run through of the basic JavaScript language constructs Code using the powerful object-oriented feature in JavaScript Master DOM manipulation, cross-browser strategies, and ES6 Understand the basic concurrency constructs in Javascript and best performance strategies Harness the power of patterns for tasks ranging from application building to code testing Build large-scale apps seamlessly with the help of reactive patterns Explore advanced design patterns, including dependency injection Develop more powerful applications with currying and function composition Create more reliable code with closures and immutable data In Detail JavaScript is a high-level, dynamic, untyped, lightweight, and interpreted programming language and functional programming is a style that emphasizes and enables smarter code that minimizes complexity and increases modularity. It's a way of writing cleaner code through clever ways of mutating, combining, and using functions. And JavaScript provides an excellent medium for this approach. By learning how to expose JavaScript's true identity as a functional language, we can implement web apps that are more powerful, easier to maintain and more reliable. The java script: Functional Programming for JavaScript Developers course will take you on a journey to show how functional programming when combined with other techniques makes JavaScript programming more efficient. The first module Mastering JavaScript, stress on practical aspects of Javascript development like - Functions and Closures, Runtime debugging techniques, project layout, events and DOM processing, build tools, Object-oriented pa...